The Addition of Lemuru Fish Oil in Bran Suspension to Successful Induction of M. macrocopa Ephippia Production - Reni Oktaviani; Ahmad Shofy Mubarak; Sudarno Sudarno (Journal of Aquaculture and Fish Health, 2020)
The production M. macrocopa ephippia limited by availability of poly unsaturated fatty acids (PUFAs) in feed. The lack amount of ω-3 fatty acids in rice bran suspension limits ephippia production. Lemuru fish oil containing EPA has potential to enrich in rice bran suspension to increase ephippia production. The purpose of this study to determine the affect addition of lemuru fish oil in rice bran suspension and the optimal concentration of lemuru fish oil in rice bran suspension which results the highest ephippia production. This study used Completely Randomized Design (CRD) method with 5 treatments adding fish oil in rice bran suspension of 0%, 1.5%, 3%, 4.5%, and 6%), with 4 replications. Sexual female offspring are produced from cultures with density 660 ind /L with regulated feed concentration. Furthermore, offspring are cultured with feed according the treatment. During the culture, daily production, total production and production ephippia per  parent. These results indicate addition of lemuru fish oil to rice bran suspension as feed of  M. macrocopa affect the production ephippia. The addition of lemuru fish oil with concentration  6ml / 100g in rice bran produce the highest total M. macrocopa ephippia production  (3452 ± 43.0 grains / Liter)